Unusual presentation of basal cell carcinoma on face - Jeevankumar B; Thappa Devinder (Wolters Kluwer Medknow Publications, 2005)
A 63-year-old woman presented with an asymptomatic slowly growing lesion on the nose of 5 years duration. On cutaneous examination, the nose and adjacent left cheek showed a single, large, ill-defined, indurated annular plaque with distinct margin. Close examination of the edges of the plaque revealed thread like raised border. A biopsy from the edge of the plaque showed buds and irregular proliferations of tumor tissue attached to the undersurface of the epidermis and masses of epitheliometous basal cells in the dermis surrounded by clear-cut spaces and dermal fibrotic changes. The peripheral cell layer of the tumor formations showed palisading. These histologic features were consistent with basal cell carcinoma. We, herewith report this case of overlap of superficial spreading BCC with morphea-like basal cell carcinoma for its rarity and unique features.